2011
DOI: 10.1159/000333807
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Highly Efficient and Reproducible Round-Window Stimulation in Humans

Abstract: Round-window stimulation is a new clinical approach for the application of active middle-ear implants. To investigate factors influencing the efficiency of round-window stimulation, experiments in 6 human temporal bones were performed with different actuator geometries and coupling conditions. The experiments show that the amplitude ratio between stapes and round-window actuator vibration is most efficient when using a 1.0-mm diameter rod with a 30° inclined tip geometry and an attached silicone pad. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…On the basis of our findings reported here, we propose that the pressure shunting occurred through the area of the RW which remained exposed. This proposal is also supported by the findings of Schraven et al [32], who tested different sized actuator tips and their coupling to the RW. Schraven et al [32] found that stimulation by actuators with tip sizes well below the dimensions of the RW resulted in reduced stapedial movements compared with those tips that covered most of the RW.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the basis of our findings reported here, we propose that the pressure shunting occurred through the area of the RW which remained exposed. This proposal is also supported by the findings of Schraven et al [32], who tested different sized actuator tips and their coupling to the RW. Schraven et al [32] found that stimulation by actuators with tip sizes well below the dimensions of the RW resulted in reduced stapedial movements compared with those tips that covered most of the RW.…”
Section: Discussionsupporting
confidence: 71%
“…This proposal is also supported by the findings of Schraven et al [32], who tested different sized actuator tips and their coupling to the RW. Schraven et al [32] found that stimulation by actuators with tip sizes well below the dimensions of the RW resulted in reduced stapedial movements compared with those tips that covered most of the RW. This result could be accounted for if the free exposed area of the RW acted as a pressure shunt.…”
Section: Discussionsupporting
confidence: 71%
“…To guarantee reproducible positioning of the temporal bone and to control the relative position of the temporal bone and its azimuthal angle with respect to the LDV beam, the specimen was placed on an adjustment-stage setup composed of an upper section (three-axis goniometric adjustment stage) and a lower section (rotary table and an xyz-translational stage) (16,17). The spatial angle between the surface normal of the stapes footplate and the LDV laser beam was estimated to be 40 to 60 degrees.…”
Section: Measurement Setupmentioning
confidence: 99%
“…To guarantee reproducible positioning of the temporal bone and to control the relative position of the temporal bone and its azimuthal angle with respect to the LDV beam, the specimen was placed on an adjustment-stage setup composed of an upper section (3-axis goniometric adjustment stage) and a lower section (rotary table and an xyz-translational stage) [Schraven et al, 2011;Schraven et al, 2012]. The spatial angle between the surface of the stapes footplate and the LDV laser beam was 40-60°.…”
Section: Measurement Setupmentioning
confidence: 99%